Does Firm Size Buffer Tax Aggressiveness? Examining Financial Distress and Capital Intensity - Benny Oktaviano; Dian Sulistyorini Wulandari; Arthamivia Brilyana Rasidi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study investigates the relationships between financial distress, capital intensity, and tax aggressiveness, focusing on the moderating role of firm size. Utilizing a sample of property and real estate companies listed on the Indonesia Stock Exchange from 2021 to 2023, the research employs quantitative methods to analyze the influence of financial distress and capital intensity on tax aggressiveness. The findings reveal that financial distress significantly increases tax aggressiveness, indicating that firms facing economic challenges are more likely to pursue aggressive tax strategies to enhance their cash flow. Additionally, capital intensity is positively associated with tax aggressiveness, as firms leverage their capital assets for potential tax benefits. However, the study finds that firm size does not significantly moderate the relationships between financial distress or capital intensity and tax aggressiveness, suggesting that the effects of these variables are consistent across different firm sizes. These results underscore the complex dynamics of corporate tax behavior and highlight the need for firms to carefully consider their tax strategies in the context of financial conditions and capital structure. The research contributes to a deeper understanding of tax aggressiveness in emerging markets and provides implications for corporate managers and policymakers regarding tax planning and regulation